Diabetes Mellitus dengan Status Gizi (Underweight) dalam Meningkatkan Resiko Kasus Tuberkulosis : Studi Kasus Kontrol di Puskesmas Mulyorejo - Romaden Marbun; Wisoedhanie Widi; Vincensia Dea (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2021)
The incidence and prevalence of tuberculosis (TB) and Diabetes Mellitus (DM) now is increasing rapidly in the world. The International Diabetes Federation reports that people with Diabetes Mellitus have a higher risk of developing tuberculosis. There are several risk factors that are thought to increase the incidence of tuberculosis, one of which is Diabetes Mellitus (DM). This study aims to determine the relations between DM and the incidence of TB at Puskesmas Mulyorejo Malang. The research design was case control. The sample consisted of 114 respondents covering 57 for the control group and 57 for the case group. Data analysis using logistic regression. In the tuberculosis group, the percentage of respondents with DM was 64.9%, while in the group who did not suffer from tuberculosis, the percentage of respondents with DM was 24.6%. In this study, DM interacted with nutritional status (underweight). Means, at the same smoking habit, the relationship between DM and TB incidence is different according to the nutritional status of the respondent. For the underweight respondents, DM has a 20.0 times higher chance of developing TB than respondents who do not have diabetes. For the future, the researchers who will conduct similar research can discusse more and also improve this research with broader research variables in form of correlation. Diabetes mellitus is a disease that can cause a decrease in the cellular immune system. Keywords: diabetes mellitus; tuberculosis ABSTRAK Insidensi dan prevalensi penyakit tuberkulosis (TB) dan Diabetes Mellitus (DM) meningkat cepat di dunia. International Diabetes Federation melaporkan penderita Diabetes Mellitus berisiko lebih tinggi untuk berkembang menjadi tuberkulosis. Terdapat beberapa faktor resiko yang diduga dapat meningkatkan kejadian Tuberkulosis, salah satunya adalah Diabetes Mellitus (DM) Penelitian ini bertujuan untuk mengetahui Hubungan antara DM dengan kejadian TB di Puskesmas Mulyorejo Malang. Desain penelitian adalah case control. Sampel berjumlah 114 responden yang meliputi 57 untuk kelompok kontrol dan 57 untuk kelompok kasus. Analisis Data menggunakan regresi logistik. Pada kelompok tuberkulsosis, presentase responden dengan DM sebesar 64,9%, sedangkan pada kelompok yang tidak menderita tuberkulosis, persentase responden dengan DM sebesar 24,6%. Pada penelitian ini, DM berinteraksi dengan status gizi (underweight). Artinya, pada kebiasaan merokok yang sama, hubungan DM dengan kejadian TB berbeda menurut status gizi responden. Pada responden yang underweight, DM memiliki peluang 20,0 kali lebih tinggi untuk terjadi TB dibandingkan responden yang tidak DM. Diabetes mellitus merupakan suatu penyakit yang dapat menyebabkan penurunan sistem imunitas selular. Kata kunci: diabetes melitus; tuberkulosis